Life is strange - Hertz, Issac; Jakubowicz, Alan; Cirino, Zachary; Lookback Productions; Soundview Media Partners ([Santa Monica, Calif.?] : Lookback Productions, 2012)
Life is Strange is an independent documentary film that tells the stories of Jewish people who were displaced by the Second World War, but concentrates on the vibrant cultural and family life they experienced in their youth that ultimately was most influential in their lives. It explores the connection between old age and childhood, asking questions about what remains of childhood in our later years, as well as engaging interesting issues of self-identity, Jewish identity, and the struggle to make any sense of our experience. It includes interviews with Shimon Peres, President of the state of Israel, Walter Kohn, Nobel laureate in Chemistry, Robert Aumann, Nobel Laureate in economics, and children's book author Uri Orlev.
Originally released as a motion picture in 2012.
Narrators: Zachary Cirino, Isaac Hertz.
Shimon Peres, Walter Kohn, Robert Aumann.
Editors, Alain Jakubowicz, Artem Zuev ; music, Jean-Michel Guirao.
In English, Yiddish, and Hebrew with English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed May 5, 2017).
Keywords: World War, 1939-1945 -- Jews; Holocaust survivors -- Personal narratives; Jews -- Personal narratives; Jews -- Identity; Jewish children in the Holocaust; Jewish children -- Europe -- 20th century -- Personal narratives; Jews -- Social life and customs; Nonfiction films; Historical films; Biographical films; Documentary films; Feature films; Internet videos; Streaming video